Multimedia Development Android-based Learning of History at SMP Negeri 2 Paranggupito - Sevinda Anandya Yudayana; Relly Prihatin; Faishal Rida Kusuma (Indonesian Journal of Learning and Instructional Innovation, 2026)
History learning at the junior high school level still faces several challenges, such as low student learning interest, dominance of lecture methods, and limited use of interactive learning media. These conditions make students difficult to understand chronology, cause-effect relationships, and historical events comprehensively. This study aims to develop Android-based learning multimedia for eighth-grade history subjects at SMP Negeri 2 Paranggupito and determine the feasibility of the media based on expert validation. This research used the Research and Development (R&D) method with the ADDIE development model consisting of analysis, design, development, implementation, and evaluation stages. The product was developed using Smart Apps Creator (SAC) in the form of an Android APK application containing historical materials, images, audio, animations, and interactive quizzes. Data collection techniques included observation, interviews, and validation questionnaires. The results showed that the Android-based learning multimedia obtained a “Very Good” category based on material expert and media expert assessments, indicating that the product was feasible for use in history learning. The Android-based multimedia learning application provides a more engaging, interactive, flexible, and relevant learning experience for digital generation students.